EKSISTENSI PURA SIWA KERTHA PAYOGAN AGUNG DESA PAKRAMAN PENARUKAN KECAMATAN BULELENG KABUPATEN BULELENG - Kadek Andre Roy Nata; Komang Bella Anggreni (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
This research was carried out on the basis of researchers' interest in the existence of the great Siwa Kertha Payogan Temple in Pakraman Penarukan Village, Buleleng District, Buleleng Regency. If you look closely at this great Shiva Kertha Payogan temple, it has unique and different things from other temples. However, if seen there are still few people who want to examine the existence and meaning of this temple. Therefore, it is important to conduct research on the existence of Pura Siwa Kertha Payogan Agung. The results obtained, namely: Temple structure is divided into three parts, namely Nista Mandala, Madya Mandala and Utama Mandala. This temple has several functions such as (1) religious function, (2) social function, and (3) cultural function. The meaning contained in Pura Siwa Kertha Payogan Agung is (1) theological meaning explained by (a) the Saguna Brahman concept, and (b) theological concept of Pantheism, (2) the aesthetic meaning, (3) the meaning of harmony